Family History and Age at the Onset of Upper Urinary Tract Calculi - Ahmadi Asr Badr, Yadollah; Hazhir, Samad; Hasanzadeh, Kamaleddin (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The aim of this study was to evaluate the effect of family history on the age of urinary calculus formation and its relation with characteristics of the calculi and patients. Materials and Methods: In a cross-sectional study in Tabriz, a total of 210 patients with upper urinary tract calculi were evaluated. Their demographics and clinical characteristics and detailed information on their family history were recorded. Results: Of the patients, 28.6% had a positive family history for urinary calculi. Siblings were the majority of the affected family members (71.1%). The rate of a positive family history was slightly higher in women than in men (30.0% versus 28.1%; P = .20). The mean age at the disease onset of the men with and without a positive family history was 37.2 years versus 39.3 years, respectively (P = .20). Such a difference was not detected in the female patients, either (P = .63). In general, the calculi were more detected on the left renal unit, but more prevalent on the right side in patients with a positive family history (P = .008). No relation was found between the number and size of the calculi and the family history. Conclusion: About one-third of the patients with urinary calculi had a positive family history too. Men with affected family members are slightly more susceptible to the disease at younger ages. There might be differences in the side of the calculi and family members with a history of disease that warrants further studies.